Yayasan Sejahtera’s programmes and the hardcore poor in Kelantan / Nurul Nadhirah Anuar - Nurul Nadhirah , Anuar (2018)
This research is a study of Yayasan Sejahtera’s programmes on the hardcore poor in Bachok and Pasir Puteh, Kelantan. Yayasan Sejahtera, a non-governmental organization (NGO) has conducted a few programmes to support the basic needs of the hardcore poor in Kelantan. By using the Sustainable Livelihood Approach (SLA), this study explored the vulnerability contexts of the hardcore poor in Kelantan, assessed the assistance provided by Yayasan Sejahtera and examined the impacts of the organization’s programmes on their beneficiaries after three years. This study employed a qualitative research method through interview sessions with the beneficiaries and the key informant of Yayasan Sejahtera. Besides, the researcher also collected secondary data from Yayasan Sejahtera’s Annual Reports. Based on the interviews and findings from the annual reports, the researcher conducted triangulation of data and found that the hardcore poor in Kelantan are most vulnerable to climate change. Aside from that, it was found that materials, equipment and technical training provided to the respondents are beneficial for their economic activity. However, some respondents failed to utilize the networking opportunities provided, making them less able to withstand the vulnerability issues and to form a productive business relationship. In addition, this study found that the majority of respondents failed to continuously practice the financial management skills learned from the programmes. On the other hand, there is a gradual increase on the physical capital and slight increase on the financial capital of the respondents. The findings from this study provided an insight on the livelihood of the hardcore poor in Kelantan which is helpful in identifying their vulnerability contexts and assisting them in achieving sustainable livelihoods.